Linear light lithium battery diaphragm and preparation method thereof
By using silane coupling agent, carboxymethylcellulose and rod-shaped hydrated aluminum silicate slurry on the lithium battery separator, a dense ceramic coating is solved, and the poor affinity of the electrolyte and insufficient liquid absorption capacity of the traditional lithium battery separator is solved. The problem of this problem has achieved higher liquid absorption, liquid retention capacity and adhesion, and improved the circulation performance of lithium-ion batteries.
Patent Information
- Application Number
- CN202411757459.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional lithium battery separators have problems such as poor affinity for electrolytes, large separators, and relatively general infiltration ability and liquid absorption capacity, which cannot meet the modern needs of lithium battery separators.
A linear lightweight lithium battery separator is employed, including a coating on the base film and a coating on the base film, obtained by coating a specific slurry. The slurry consists of a silane coupling agent, carboxymethyl cellulose (CMC) and rod-shaped hydrated aluminum silicate, and is coated on the base film by an anilox roller to form a ceramic coating with a dense spatial structure.
Through the synergistic effect of silane coupling agent, carboxymethyl cellulose and rod-shaped hydrated aluminum silicate, the liquid absorption, liquid retention and adhesion of the membrane are improved, the surface density of the membrane is reduced, and thus the lithium-ion battery is improved cycling performance and capacity retention rate.
Smart Images

Figure CN119447703A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery separators, and in particular relates to a linear lightweight lithium battery separator and a preparation method thereof. Background Art
[0002] With the development of the times, new energy electric vehicles have gradually become an integral part of people's lives. As the power source of electric vehicles, the safety and endurance of lithium-ion batteries are the focus of scientific research. Lithium battery separators play an important role in lithium-ion batteries.
[0003] Traditional polyolefin separators have disadvantages such as poor affinity for electrolytes and large separator mass. Their wetting and liquid absorption abilities are average and cannot meet people's current requirements for lithium battery separators. It is imperative to develop new lithium battery separators. Summary of the invention
[0004] In view of the deficiencies of the prior art, an object of the present invention is to provide a linear and lightweight lithium battery separator.
[0005] Another object of the present invention is to provide a method for preparing the above-mentioned linear lightweight lithium battery separator.
[0006] Another object of the present invention is to provide a slurry.
[0007] The purpose of the present invention is achieved through the following technical solutions.
[0008] A linear lightweight lithium battery separator comprises: a base film and a coating on the base film, wherein the coating is obtained by coating a slurry, wherein the slurry comprises: a silane coupling agent, carboxymethyl cellulose (CMC) and rod-shaped hydrated aluminum silicate, wherein the ratio of the silane coupling agent, carboxymethyl cellulose (CMC) and rod-shaped hydrated aluminum silicate is (0.5-0.8):4:(18-20) by weight.
[0009] In the above technical solution, the length of the rod-shaped hydrated aluminum silicate is 100 to 130 microns, and the width is 200 to 600 nm.
[0010] In the above technical solution, the silane coupling agent is one or a mixture of vinyl triethyl silane, vinyl trimethoxy silane, trimethyl methoxy silane, aminopropyl trimethoxy silane, methacryloxy silane and ureidopropyl triethoxy silane.
[0011] In the above technical solution, the coating comprises stripes which are parallel to each other and arranged at intervals, the distance between adjacent stripes is 1 to 2 mm, and the width of each stripe is 4 to 5 mm.
[0012] In the above technical solution, the thickness of the coating is 1 to 6 μm.
[0013] In the above technical solution, the ratio of silane coupling agent, carboxymethyl cellulose (CMC) and rod-shaped hydrated aluminum silicate is preferably (0.5-0.6):4:(18-20) in parts by mass.
[0014] The method for preparing the above-mentioned linear lightweight lithium battery separator comprises: coating the slurry on the base film by using an anilox roller, and drying to obtain the linear lightweight lithium battery separator.
[0015] In the above technical solution, the surface of the anilox roller is provided with strip-shaped protrusions, and the depth of the protrusions is 1 to 6 μm.
[0016] In the above technical solution, during coating, the axial angle between each stripe and the anilox roller is 45°.
[0017] A slurry comprises: water, rod-shaped hydrated aluminum silicate, carboxymethyl cellulose (CMC), a silane coupling agent, a dispersant, a wetting agent and an adhesive. The ratio of the silane coupling agent, the dispersant, the water, the carboxymethyl cellulose (CMC), the rod-shaped hydrated aluminum silicate, the wetting agent and the adhesive is (0.5-0.8): 0.4: 30: 4: (18-20): 0.05: (1-5) by weight.
[0018] In the above technical solution, the dispersant is ammonium polyacrylate.
[0019] In the above technical solution, the wetting agent is a polyether siloxane wetting agent.
[0020] In the above technical solution, the adhesive is polyacrylate.
[0021] In the above technical solution, the ratio of the silane coupling agent, the dispersant, the water, carboxymethyl cellulose (CMC), the rod-shaped hydrated aluminum silicate, the wetting agent and the adhesive is preferably (0.5-0.6): 0.4: 30: 4: (18-20): 0.05: (1-5) by mass.
[0022] The method for preparing the slurry comprises: mixing water, rod-shaped hydrated aluminum silicate, carboxymethyl cellulose (CMC), a silane coupling agent, a dispersant, a wetting agent and an adhesive until uniform to obtain the slurry.
[0023] In the above technical solution, the method for preparing the slurry comprises the following steps:
[0024] Step 1, mixing water and carboxymethyl cellulose (CMC) until uniform, then adding rod-shaped hydrated aluminum silicate and a dispersant, and mixing until uniform to obtain a first solution;
[0025] In step 1, water and carboxymethyl cellulose (CMC) are mixed and stirred until uniform, and then rod-shaped hydrated aluminum silicate and a dispersant are added in sequence, and stirred and then ultrasonicated until the mixture is uniformly mixed to obtain a first solution.
[0026] Step 2: Mix the first solution, silane coupling agent and adhesive until they are uniform, then add a wetting agent and mix until they are uniform to obtain a slurry.
[0027] In step 2, the first solution, the silane coupling agent and the adhesive are mixed, ultrasonicated under stirring until uniform, and then a wetting agent is added, stirred, and ground until uniform to obtain a slurry.
[0028] Application of silane coupling agent, carboxymethyl cellulose and rod-shaped hydrated aluminum silicate to synergistically improve the liquid absorption rate, liquid retention rate and / or adhesion of the separator.
[0029] Application of silane coupling agent, carboxymethyl cellulose and rod-shaped hydrated aluminum silicate to synergistically reduce the surface density of the separator.
[0030] Application of silane coupling agent, carboxymethyl cellulose and rod-shaped hydrated aluminum silicate to synergistically improve battery capacity retention rate.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] After the slurry of the present invention is coated on the surface of the base film, a ceramic coating containing hydrated aluminum silicate is obtained. The hydrated aluminum silicate is tightly spread on the surface of the base film to form a dense spatial structure, and the silane coupling agent is between the inorganic and organic interfaces. A part of the functional groups in the silane coupling agent can react with organic molecules (polyacrylates), and another part of the functional groups can react with adsorbed water on the surface of inorganic substances (rod-shaped hydrated aluminum silicate) to form a binding layer of organic matrix-silane coupling agent-inorganic matrix, which provides a strong bonding ability and reduces the probability of lithium ions reacting with free water in the lithium battery to cause loss of active substances and reduce the capacity of the lithium ion battery. The addition of rod-shaped hydrated aluminum silicate effectively reduces the surface density of the diaphragm, thereby reducing the quality of the lithium ion battery. At the same time, the diaphragm of the present invention also has high liquid absorption, liquid retention and wettability, and the lithium ion battery has excellent cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is an electron microscope image of the separator in the lithium ion battery of Example 7;
[0034] Figure 2 This is an electron microscope image of the separator in the lithium ion battery of Example 10;
[0035] Figure 3 This is an electron microscope image of the separator in the lithium-ion battery of Example 11. DETAILED DESCRIPTION
[0036] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0037] The molecular structure of silane coupling agent is generally YR-Si(OR)3 (where Y is an organic functional group and SiOR is a silaneoxy group). Silaneoxy group is reactive to inorganic substances, while organic functional groups are reactive or compatible to organic substances.
[0038] Rod-shaped hydrated aluminum silicate is made of hard clay clinker as raw material, and is produced by melting in a resistance or arc furnace and blowing into fibers. Aluminum silicate is a kind of aluminum silicate. The length of rod-shaped hydrated aluminum silicate is 100-130 microns, the width is 200-600nm, the pH is 8-11, and the appearance is light yellow.
[0039] In the following examples, water is deionized water.
[0040] In the following examples, the base film is a PE film, and the thickness of the PE film is 9 μm.
[0041] At 26-28°C, cut the diaphragm into a size of 50mm*50mm (sample 1), weigh the mass of sample 1, and record it as the mass before immersion (g); soak sample 1 in the electrolyte for 30 minutes, take it out, and gently wipe the surface of the diaphragm with filter paper (sample 2), weigh the mass of sample 2, and record it as the mass after immersion (g); leave sample 2 for one hour, weigh it again, and record it as the mass of the liquid-retaining diaphragm (g). The values of liquid absorption rate and liquid retention rate are expressed in %:
[0042] Liquid absorption rate = (mass after immersion - mass before immersion) / mass before immersion * 100%;
[0043] Liquid retention rate = (mass of liquid retention membrane - mass before immersion) / mass before immersion * 100%.
[0044] Adhesion: Cut a diaphragm with a width of 25 mm and a length of 150 mm; cut a 3M test tape with a length of 200 mm. Stick the cut diaphragm and the 3M test tape together, keep the diaphragm flat, and peel it off at a speed of 100 mm / min. After the test, read the data of the tensile tester. Tensile tester: Dongguan Lixian Instrument Technology Co., Ltd.
[0045] Embodiment 1-2
[0046] A method for preparing a slurry comprises the following steps:
[0047] Step 1, in a planetary stirring device, water and carboxymethyl cellulose (CMC) are mixed, and stirred for 10 minutes at a rotation speed of 3300 r / min and a revolution speed of 20 r / min until uniform, and then rod-shaped hydrated aluminum silicate and a dispersant are added in sequence, first stirred for 10 minutes (rotation speed of 3300 r / min, revolution speed of 20 r / min) and then ultrasonicated in an ultrasonic device for 10 minutes (ultrasonic frequency of 5 kHz) until uniform, to obtain a first solution;
[0048] Step 2, in a planetary stirring device, the first solution, the silane coupling agent and the adhesive are mixed, and ultrasonic (ultrasonic frequency is 5kHz) is performed for 15 minutes under stirring (the stirring rotation speed is 1000r / min and the revolution speed is 20r / min) until uniform, and then a wetting agent is added, stirred at a speed of 1000r / min for 10 minutes, put into a grinder, and grind at a speed of 400r / min for 10 minutes until uniform to obtain a slurry. In terms of mass fractions, the ratio of silane coupling agent, dispersant, water, carboxymethyl cellulose (CMC), rod-shaped hydrated aluminum silicate, wetting agent and adhesive is X, the silane coupling agent is vinyl triethyl silane, the dispersant is ammonium polyacrylate, the wetting agent is a polyether siloxane wetting agent (TEGO WET 270 wetting agent), and the adhesive is polymethyl acrylate. The value of X is shown in Table 1.
[0049] Table 1
[0050] Slurry X Example 1 0.5:0.4:30:4:18:0.05:5 Example 2 0.8:0.4:30:4:20:0.05:5
[0051] Example 3
[0052] A method for preparing slurry is basically the same as that of Example 1, except that "rod-shaped hydrated aluminum silicate" is replaced by "granular hydrated aluminum silicate". The particle size of the granular hydrated aluminum silicate is 500-600 nm.
[0053] Example 4
[0054] A method for preparing slurry is basically the same as that of Example 1, except that "rod-shaped hydrated aluminum silicate" is replaced by "aluminum oxide (particles)". The particle size of the aluminum oxide (particles) is 400-500 nm.
[0055] Example 5
[0056] A method for preparing a slurry is substantially the same as that of Example 4, except that no silane coupling agent is added in Example 5. In Example 5, the ratio of the dispersant, water, carboxymethyl cellulose (CMC), alumina (particles), wetting agent and adhesive is 0.4:30:4:18:0.05:5 by weight.
[0057] Example 6
[0058] A method for preparing a slurry is substantially the same as Example 1, except that no silane coupling agent is added in Example 6. In Example 6, the ratio of the dispersant, water, carboxymethyl cellulose (CMC), rod-shaped hydrated aluminum silicate, wetting agent and adhesive is 0.4:30:4:18:0.05:5 by weight.
[0059] Embodiments 7 to 10
[0060] A lithium ion battery (a 606090 type lithium ion battery with a capacity of 4000mAh and a nominal voltage of 3.7V) comprises: a positive electrode, a negative electrode, a separator and an electrolyte, wherein the method for preparing the positive electrode is: using a wet process to mix N-methylpyrrolidone, a ternary material (NCM523), a positive electrode conductive agent (conductive carbon black) and a positive electrode binder (polyvinylidene fluoride), stirring at a rotation speed of 1500r / min and a revolution speed of 20r / min, and then ultrasonicating at a frequency of 7kHz for 30min to obtain a positive electrode slurry, wherein the ratio of N-methylpyrrolidone, the ternary material, the positive electrode conductive agent and the positive electrode binder is 10:8:1:1 in terms of mass fraction. 1.5 g of positive electrode slurry was coated on an aluminum foil substrate (91.5 mm*1 m), dried in a constant temperature oven to form a positive electrode coating, and then the positive electrode coating was firmly pressed with the aluminum foil substrate by roller pressing to obtain a positive electrode; the method for preparing the negative electrode was as follows: N-methylpyrrolidone, graphite, a negative electrode conductive agent (acetylene black) and a negative electrode binder (polymethyl acrylate) were mixed by a wet process, stirred at a rotation speed of 1500 r / min and a revolution speed of 20 r / min, and then ultrasonicated at a frequency of 7 kHz for 30 minutes to obtain a negative electrode slurry, wherein the ratio of N-methylpyrrolidone, graphite, negative electrode conductive agent and negative electrode binder was 10:8:0.8:1.2 by mass. 1.5g of negative electrode slurry was coated on a copper foil substrate (91.5mm*1.2m), dried in a constant temperature oven to form a negative electrode coating, and then the negative electrode coating and the copper foil substrate were firmly pressed by roller pressing to obtain a negative electrode; the electrolyte was a mixture of electrolyte and solvent, the electrolyte in the electrolyte was lithium hexafluorophosphate LiPF6, the solvent was ethylene carbonate (EC), and the concentration of the electrolyte in the electrolyte was 1mol / L. The preparation method of the diaphragm included: using an anilox roller to coat the slurry on one side of the base film, drying at 50°C for 10min, and obtaining a coating with a thickness of 3μm on the base film to obtain a diaphragm. The slurry was one of Examples 1 to 4.
[0061] The surface of the anilox roller is provided with strip-shaped protrusions so that the upper part of the coating is formed with parallel and spaced stripes, wherein the distance between adjacent stripes is 1.2 mm, the width of each stripe is 4.5 mm, and during coating, the length direction of each stripe is at an angle of 45° to the axial direction of the anilox roller, and the protrusion depth is 3 μm.
[0062] Table 2
[0063] Lithium-ion battery Slurry for preparing diaphragm Example 7 Example 1 Example 8 Example 2 Example 9 Example 3 Example 10 Example 4
[0064] Embodiment 11
[0065] A lithium ion battery is substantially the same as that of Example 7, except that the separator is different. The preparation method of the separator in Example 11 comprises: coating the slurry of Example 5 on a base film on one side using a conventional gravure roller (with a groove depth of 3 μm), drying at 50° C. for 10 min, obtaining a coating with a thickness of 3 μm on the base film, and obtaining the separator of Example 11.
[0066] Example 12
[0067] A lithium ion battery is basically the same as Example 7, the only difference being that the slurry is different. The slurry used in Example 12 is the slurry prepared in Example 6.
[0068] Embodiment 13
[0069] A lithium ion battery is substantially the same as that of Example 7, except that the separator is different. The preparation method of the separator in Example 13 comprises: coating the slurry of Example 1 on a base film on one side using a conventional gravure roller (with a groove depth of 3 μm), drying at 50° C. for 10 min, obtaining a coating with a thickness of 3 μm on the base film, and obtaining the separator of Example 13.
[0070] Figure 1 This is an electron microscope image of the separator in the lithium-ion battery of Example 7. Figure 2 This is an electron microscope image of the separator in the lithium ion battery of Example 10. Figure 3 This is an electron microscope image of the separator in the lithium-ion battery of Example 11.
[0071] The slurries prepared in Examples 1 to 6 were tested. The test results are shown in Table 3. The test conditions were: 20 to 28° C.; relative humidity: 55 to 65%; atmospheric pressure: 90 to 98 kPa.
[0072] Table 3
[0073]
[0074]
[0075] As shown in Table 3, the particle size D50 of the slurry in Example 1 is 7.12 μm; the particle size D50 of the slurry in Example 2 is 7.03 μm; the particle size D50 of the slurry in Example 3 is 0.98 μm; the particle size D50 of the slurry in Example 4 is 0.96 μm; the particle size D50 of the slurry in Example 5 is 0.81 μm, and the particle size D50 of the slurry in Example 6 is 5.32 μm. After the surface of the rod-shaped hydrated aluminum silicate is coated with silane, the particle size of the slurry formed will increase.
[0076] The liquid absorption rates of the separators in the lithium-ion batteries obtained in Examples 7 to 13 are shown in Table 4 (three tests were performed for each example).
[0077] Table 4
[0078]
[0079]
[0080] The liquid retention rates of the diaphragms in Examples 7 to 13 are shown in Table 5 (three tests were performed for each example).
[0081] Table 5
[0082]
[0083]
[0084] It can be seen from Table 4 and Table 5 that the separator in Example 7 has the best liquid absorption rate and liquid retention rate. The synergistic effect of the silane coupling agent and the rod-shaped hydrated silicate greatly improves the ability of the separator to absorb and retain the electrolyte.
[0085] The experimental data of the lithium-ion batteries prepared in Examples 7 to 13 are shown in the following table.
[0086] Table 6
[0087]
[0088] It can be clearly seen from Table 6 that the mass of the diaphragm prepared using the slurry of Example 1 and Example 2 is the smallest. For example, the mass of the diaphragm in Example 7 (using rod-shaped hydrated aluminum silicate) is 16% lower than that of the diaphragm in Example 10 (using aluminum oxide), thereby reducing the mass of the lithium-ion battery.
[0089] The adhesion between the coating and the base film in the lithium ion batteries prepared in Examples 7 to 13 is shown in Table 7.
[0090] Table 7
[0091]
[0092]
[0093] It can be seen from Table 7 that the embodiments containing silane coupling agents in the slurry have good bonding strength, which is higher than the embodiments without adding silane coupling agents in the slurry (Examples 11 and 12), among which the embodiments in which rod-shaped hydrated aluminum silicate and silane coupling agents are combined (Examples 7 and 8) have the best bonding strength.
[0094] Table 8 (Cyclic test at current density J = 25.97 A / ㎡)
[0095]
[0096]
[0097] It can be seen from Table 8 that after more than 200 cycles, the capacity retention rates of Examples 7 and 8 are both above 85%, which are better than those of other examples. The lithium-ion batteries prepared in Examples 7 and 8 have better cycle capabilities.
[0098] The parameters of the lithium ion battery separator prepared in Example 7 are as follows:
[0099]
[0100] When "vinyltriethylsilane" in Example 1-2 is replaced with "one of vinyltrimethoxysilane, trimethylmethoxysilane, aminopropyltrimethoxysilane, methacryloxysilane and ureidopropyltriethoxysilane", the same technical effect as that of Example 1-2 can be obtained.
[0101] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A linear lightweight lithium battery separator, characterized in that: include: The base film and the coating on the base film are obtained by coating with a slurry, the slurry includes: a silane coupling agent, carboxymethyl cellulose and rod-shaped hydrated aluminum silicate, and the ratio of the silane coupling agent, carboxymethyl cellulose and rod-shaped hydrated aluminum silicate is (0.5-0.8):4:(18-20) by weight.
2. The linear lightweight lithium battery separator according to claim 1, characterized in that: The length of the rod-shaped hydrated aluminum silicate is 100 to 130 microns and the width is 200 to 600 nm.
3. The linear lightweight lithium battery separator according to claim 1, characterized in that: The silane coupling agent is one or a mixture of vinyl triethyl silane, vinyl trimethoxy silane, trimethyl methoxy silane, aminopropyl trimethoxy silane, methacryloxy silane and ureidopropyl triethoxy silane.
4. The linear lightweight lithium battery separator according to claim 1, characterized in that: The coating comprises stripes which are parallel to each other and arranged at intervals, the distance between adjacent stripes is 1 to 2 mm, and the width of each stripe is 4 to 5 mm.
5. The method for preparing a linear lightweight lithium battery separator according to any one of claims 1 to 4, characterized in that: include: The slurry is coated on the base film by an anilox roller and dried to obtain a linear and lightweight lithium battery separator.
6. A slurry, characterized in that: include: Water, rod-shaped hydrated aluminum silicate, carboxymethyl cellulose, silane coupling agent, dispersant, wetting agent and adhesive, calculated by mass, the ratio of silane coupling agent, dispersant, water, carboxymethyl cellulose, rod-shaped hydrated aluminum silicate, wetting agent and adhesive is (0.5-0.8):0.4:30:4:(18-20):0.05:(1-5).
7. The method for preparing the slurry according to claim 6, characterized in that: include: Water, rod-shaped hydrated aluminum silicate, carboxymethyl cellulose, a silane coupling agent, a dispersant, a wetting agent and an adhesive are mixed until uniform to obtain a slurry.
8. Application of silane coupling agent, carboxymethyl cellulose and rod-shaped hydrated aluminum silicate to synergistically improve the liquid absorption rate, liquid retention rate and / or adhesion of the diaphragm.
9. Application of silane coupling agent, carboxymethyl cellulose and rod-shaped hydrated aluminum silicate to synergistically reduce the surface density of the diaphragm.
10. The application of silane coupling agent, carboxymethyl cellulose and rod-shaped hydrated aluminum silicate to synergistically improve the battery capacity retention rate.
Citation Information
Patent Citations
Preparation method of ceramic coated diaphragm and application of ceramic coated diaphragm in lithium battery
CN115863917A
Battery isolating membrane, preparation method thereof and energy storage device
CN117895186A
Diaphragm coating slurry for solid-state battery and preparation method of diaphragm coating slurry
CN119009380A
Composition comprising thermoplast and aluminum silicate hydrate as reinforcing filler, useful for preparation of e.g. boards, films or tubes, includes maleic anhydride-modified thermoplast as adhesion promoter
DE10305557A1
Flotation Method for Recovering Lithium-Ion Battery Cathode Material from Recycled Lithium-Ion Batteries and Scrap
US20230387489A1